Controle e monitoramento de um microssistema fotovoltaico off-grid para iluminação de baixa potência utilizando IoT - Franciscis, Kevin Guimarães de (Brasil, 2022)
The evolution of the connection speeds in internet networks allows several applications of internet of things, since a stable and fast connection is essential in these applications, the use of sensors for monitoring is one of the possible applications. In photovoltaic systems, it is important to obtain data of energy generation and consumption, in addition to control loads connected to the system, this allows more previsibility of expenses and maintenance of the system. This work consists in the development of an off-grid photovoltaic microsystem for low power lighting using the integration between the Blynk platform and the ESP32 microcontroller. For the development of the data used were used modules and sensors for the projects of monitoring of the system, the monitored quantities were: voltage, current, power, generation and consumption of energy. The Blynk platform was chosen for the elaboration of a panel for web and mobile, organizing monitoring data and allowing to control load connected to the system. As to the architecture, a charge controller was used to charge the battery keeping protection of overcharge and over-discharge, in addition a voltage regulator allowed to feed a 12 V lamp to drive it through a relay module. The system uses two solar panels in parallel for power generation and the INA219 sensors with the I2C protocol to obtain the desired parameters. The system was able to feed a load for a determined daily period of time even in the worst month of solar incidence, in addition the data obtained allowed to monitor generation, energy consumption and to trigger the load remotely.